Global Leading and Competencies of Global Leaders - Markasović, Dorotea; Podrug, Najla; Aleksić Fredotović, Ana (Naše gospodarstvo/Our economy, 2024)
Global leading and leadership are two of the most relevant topics in contemporary management literature, as shown by the scientific interest and the number of papers that reflect this topic from several different points of view. This paper's purpose was to review the current research and papers published in this field in the last decade. For this purpose, visualization was done in the VOSviewer application. Findings show that the frequency of publication had doubled in the analyzed period, with the following competencies considered the most important ones for global leaders: a global mindset, emotional intelligence, high ethical standards, fairness, empowering individuals in the team, and caring for your team. The paper provides insight into general trends in research and key research conclusions that have implications and applications in the real sector. It proposes directions for future research based on detected research gaps.
Keywords: Leadership competencies; Global leading; Global leaders; Bibliometric analysis